The Second Coming, Successful Life, and the Sweetness of Guinea: Evangelical Thoughts about the Future in Guinea-Bissau - Formenti, Ambra (Journal of Religion in Africa, 2017)
Hope, aspirations, and drive to the future have recently been the focus of academic concern about the ways in which people are thinking and producing their future in a time of great uncertainty. By exploring the distinct ways in which evangelical believers in Guinea-Bissau are engaged in imagining their future, this article aims to portray evangelical Christianity as a source of aspirations and visions of possible futures in contemporary Africa. Moreover, by comparing the programme of cultural and social regeneration pursued by nationalists in the 1960s and ’70s and the current evangelical project of personal and collective redemption, I argue that evangelical churches are promoting a politics of hope that translates Amílcar Cabral’s legacy in their own terms. Finally, I show how, in the wake of the failure of nationalist narratives, evangelical churches are fostering an emerging conceptualization of modernity as connectivity that underlies new dreams of a better future.
free
Keywords: Christianity and Islam; Culture and religion; Evangelistic work; Guinea-Bissau.; Kingdom of God